Components of Strategic Information Management Implementation in Institutions - Ali, Syuhada; Nadzirah Juhari, Noor; Atiqah Hassan Basri, Nur; Farik Mat Yatin, Saiful; Hussin, Norhayati; Huda Md Yatim, Nurul; Razilan Abdul Kadir, Mohd (International Journal of Engineering and Technology, 2018)
In several recent literatures, it reported that Strategic Information Management (SIM) might only happen within the institutions context of the existence of strategies plan. Many institutions may not realize that they have implemented this concept and adapt this to their daily routine in running their services and product. Through the advances of IT investment in the institutions, they can keep up with and better differentiate from their competitors. Investment in IT improved their productivity. The improvement of SIM plan is needed in beneficial since the IT requirements constantly change. This article is discussing three (3) different institutions which is medical institutions, banking institutions, and government agencies that catching up with the global trends in utilization of the information technology. This strategy is a phenomenon known as Strategic Information Management (SIM) to the researchers in the field of information management.Â Â